Effect of Particle Size of B4C Reinforcement on Ti-6Al-4V Sintered Composite Prepared by Mechanical Milling Method. Issue 1 (2nd January 2017) - Selvakumar, N.; Ramkumar, T.
ABSTRACT: In this study Ti, Al, V and B4 C powders were milled separately in ball mill for various time periods. The powder morphology was tested by particle size analysis (PSA), FTIR and SEM studies in every one hour interval. Finally the individual powders were mixed on a weight basis to produce novel Ti-6Al-4V-B4 C composite precursor and fabricated compacts were heat treated at 900°C. The microstructural features and mechanical properties of the sintered compacts were ascertained by microhardness and SEM studies. It was observed that with increase in milling time and B4 C reinforcement of 10 wt% yields a significant improvement of microhardness as well as homogeneous microstructure in the sintered composite. GRAPHICAL ABSTRACT: